SARS-CoV-2 uses CD4 to infect T helper lymphocytes - Brunetti, Natalia S.; Davanzo, Gustavo G.; de Moraes, Diogo [UNESP]; Ferrari, Allan J R; Souza, Gabriela F.; Muraro, Stéfanie Primon; Knittel, Thiago L.; Boldrini, Vinicius O.; Monteiro, Lauar B.; Virgílio-da-Silva, João Victor; Profeta, Gerson S.; Wassano, Natália S; et al. (eLife, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the agent of a major global outbreak of respiratory tract disease known as Coronavirus Disease 2019 (COVID-19). SARS-CoV-2 infects mainly lungs and may cause several immune-related complications, such as lymphocytopenia and cytokine storm, which are associated with the severity of the disease and predict mortality. The mechanism by which SARS-CoV-2 infection may result in immune system dysfunction is still not fully understood. Here, we show that SARS-CoV-2 infects human CD4+ T helper cells, but not CD8+ T cells, and is present in blood and bronchoalveolar lavage T helper cells of severe COVID-19 patients. We demonstrated that SARS-CoV-2 spike glycoprotein (S) directly binds to the CD4 molecule, which in turn mediates the entry of SARS- CoV-2 in T helper cells. This leads to impaired CD4 T cell function and may cause cell death. SARS-CoV-2-infected T helper cells express higher levels of IL-10, which is associated with viral persistence and disease severity. Thus, CD4-mediated SARS-CoV-2 infection of T helper cells may contribute to a poor immune response in COVID-19 patients.
Keywords: COVID-19; human; immunology; inflammation; T cells; virus infection